Comparison of the biological effects of exogenous and endogenous 1, 25-dihydroxyvitamin D3 on the mature osteoblast cell line MLO-A5. Issue 164 (November 2016) - Yang, Dongqing; Anderson, Paul H.; Turner, Andrew G.; Morris, Howard A.; Atkins, Gerald J.
Highlights: Both endogenous and exogenous 1, 25D display anabolic effects on MLO-A5 cells. Endogenous and exogenous 1, 25D display distinct pharmacodynamics for induction of Cyp24a1 mRNA. mRNA of some genes are induced by lower endogenous 1, 25D levels compared to exogenous 1, 25D Abstract: Clinical and animal data indicate that serum 25-hydroxyvitamin D3 (25D) exerts an anabolic effect on bone while serum 1α, 25-dihydroxyvitamin D3 (1, 25D) stimulates bone mineral loss, although the mechanism responsible for these divergent actions is unknown. Biological effects of 25D on bone cells are dependent on the local conversion to 1, 25D by the 25-hydroxyvitamin D-1α-hydroxylase enzyme, CYP27B1. Therefore, identification of possible differential activities of locally produced and exogenously supplied 1, 25D in bone is likely to be informative for guiding optimal administration of vitamin D supplements for bone health. The mature osteoblastic cell line MLO-A5 expresses both the vitamin D receptor ( Vdr ) and Cyp27b1, and therefore is a suitable model for comparing the activities of 1, 25D arising from these sources. Biologically, exogenous and endogenous sources of 1, 25D have similar effects on proliferation, mineralisation and induction of a range of genes by MLO-A5 osteoblasts under osteogenic conditions although endogenous 1, 25D levels are markedly lower than exogenous levels. Significant differences of pharmacokinetics and pharmacodynamics of 1, 25D are evident between these two sources particularly in terms of modulating gene expression for Cyp24a1 and other genes largely expressed by embedded osteoblasts/osteocytes suggesting that endogenously synthesised 1, 25D is more efficiently utilised by the differentiating osteoblast.